Adaptive exponential weighted composite sliding mode-based direct yaw moment control for four-wheel independently actuated autonomous vehicles - Zhengyong Tao; Mingming Wu; Min Qu; Hui Wu; Banglai Sun; Deqiang Xie; Zhongzhi Tong (PLoS ONE, 2025)
This paper introduces a novel Direct Yaw Moment Control (DYC) scheme for autonomous vehicles with Four-Wheel Independent Actuation (FWIA). In the upper-layer control strategy, an Adaptive Exponential Weighted Composite Sliding Mode Controller (AEWC-SMC) is proposed by incorporating a nonlinear weighting factor into the sliding mode surface and designing a composite reaching law. For the lower-layer torque allocation, a Dynamic Weight Minimum Energy Allocation (DWMEA) method is developed, which achieves optimal four-wheel torque distribution without iterative computation. By formulating the objective function to minimize weighted energy consumption and introducing adaptive dynamic weight parameters that account for vertical load, steering angle, and vehicle speed, this method adaptively realizes optimal torque allocation. MATLAB/Simulink simulation results demonstrate that compared with traditional Sliding Mode Control (SMC) schemes, the proposed control strategy exhibits higher tracking accuracy, faster convergence speed, and enhanced handling stability.